Edukasi gizi menggunakan media booklet dengan atau tanpa konseling terhadap pengetahuan orangtua dan konsumsi sayur dan buah anak prasekolah di wilayah urban - Herni Dwi Herawati; Azhari Silvia Novita Anggraeni; Nurul Pebriani; Arantika Meidya Pratiwi; Tri Siswati (Jurnal Gizi Klinik Indonesia, 2021)
Nutrition education using booklet media with and without counseling on parental knowledge, amount and frequency of consumption of vegetables and fruits of preschool children in urban areasBackground: Consumption of vegetables and fruit in preschool children in Indonesia is still less than recommended. Nutrition education through booklets and counseling media will clarify information and understanding of parents about the importance of consuming vegetables and fruit in preschool children, resulting in parental feeding behavior to increase the amount and frequency of consumption of vegetables and fruits in preschool children. Purpose: This study aims to determine the effect of nutrition education using booklet media with counseling and without counseling on parental knowledge, amount, and frequency of consumption of vegetables and fruits of preschool children in urban areas. Methods: This type of research was a quasi-experimental research design with pre and post-test with the control group. The selection of respondents used purposive sampling to select the sub-districts that had the percentage of excess nutrition in Yogyakarta, namely the Danurejan District, and simple random sampling to choose children and preschools (kindergarten). The number of respondents was 56 people consisting of 28 experimental and 28 controls from 4 kindergartens. Nutrition education in the experimental group gave booklets and counseling, once for 30-60 minutes and at each respondent's home. The control group was only assigned a booklet without counseling. The instruments used consisted of booklets, knowledge questionnaires, and SQ-FFQ. The statistical tests used were paired t-test, Wilcoxon, Mann Whitney, independent t-test, and Pearson. Results: This study showed increased parental knowledge before and after nutrition education in the experimental group (p<0.05). In addition, the amount and frequency of consumption of vegetables and fruits of preschool children in the experimental group increased between before and after being given nutrition education (p<0.05). Knowledge, amount, and frequency of consumption of vegetables and fruit also showed differences between the experimental and control groups (p<0.05). Conclusions: Nutrition education using booklets and counseling media affects parents' knowledge and the amount and frequency of consuming vegetables and fruit in preschool children compared to using only booklets without counseling.